The Social Construction of Threats. The Iran Nuclear Crisis as a Textbook Example for Jack Mezirow’s Transformative Learning Theory - Andreas Bock; Saskia Eschenbacher (Adult Education Research Conference, 2014)
Perception matters for research and analysis because the image of a state (non-state actor) as aggressive and the perceptions of its intentions as aggressive are mutually reinforcing. We will use an interdisciplinary perspective combining political science and adult education research, which we believe has the potential for further policy advice.